Efeitos de bloqueadores neuromusculares não despolarizantes em jabuti chelonoidis carbonaria - Alves, Lorena Borges (2015)
The pharmacological contention of turtles for routine anamnesis, diagnostics or therapeutic procedures is often required in zoos or in supporting wild and exotic animals. This study aimed to evaluate the effects of: rocuronium (0.25 and 0.5 mg/ kg/ IM), pancuronium (0.02 and 0.04 mg/ kg/ IM) and atracurim (0.6 and 0.8 mg/ kg/ IM) on heart and breathing rates; eyelid and pupillary reflexes, cloacal relaxation, straightening reflex, movements and painful sensibility. Around 60 tortoises were used and divided into three groups. Each group was composed from 20 animals subjected to a different drug. To reverse the effect of blocking, neostigmine was used (0.07 mg/ kg/ IM). The administration of rocuronium decreased respiratory rate without causing apnea. Neither the heart rate, nor eyelid and pupillary reflexes were affected. The administration of 0.25 mg/kg paralyzed movements, although a complete muscle relaxation was not observed. With 0.5 mg/kg beyond paralysis, a complete muscular relaxation and easiness in manipulation the animals were noted. The pancuronium decreased respiratory rate and may cause apnea at 0.04 mg/kg; while heart rate was not significantly affected. In both 0.02 mg/kg and 0.04 m/kg it caused loss on the straightening reflex, easiness in manipulation of the animals still, locomotion was inhibited. Atracurium did not statistically changed breathing and heart rate, cloacal relaxation, eyelid and pupillary reflexes, muscle relaxation, straightening reflex, animal locomotion neither painful sensibility.